PENGARUH PENERAPAN KEPEMILIKAN MANAJERIAL, PROFITABILITAS, UKURAN PERUSAHAAN TERHADAP KUALITAS LABA PADA SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020 – 2021 - Mutiara Ramadhan; Sri Zulaihati; Mardi Mardi (International Journal of Multidisciplinary Research and Literature, 2023)
This study aims to determine Managerial Ownership, Profitability, Company Size on Earning Quality of financial sector companies listed on the IDX. The data collection technique used is the source of library data by collecting data using documentary studies. The population in this study are financial sector companies listed on the Indonesia Stock Exchange in 2020-2021 with a total of 168 companies. The data is obtained by collecting data on the annual financial statements of financial sector companies on the IDX website. The sample used was 66 companies using non-probability sampling and the Slovin formula. The results showed that managerial ownership and firm size have no significant effect on earnings quality. While profitability have a negative and significant effect on earnings quality. The coefficient of determination describes the ability of managerial ownership, profitability, and company size that affect earnings quality by 75.2% while the rest is influenced by other factors that have not been studied.